2001
DOI: 10.1081/bio-100104233
|View full text |Cite
|
Sign up to set email alerts
|

Pluronic F-68 Enhanced Shoot Regeneration in a Potentially Novel Citrus Rootstock

Abstract: The effects have been studied in vitro of the non-ionic, co-polymer surfactant, Pluronic F-68, on shoot regeneration and bud induction in epicotyl and cotyledon explants of Citrus depressa, a potential alternative rootstock to C. jambhiri for commercial Citrus. Supplementation of Murashige and Skoog (1962)-based, agar-solidified shoot regeneration/bud induction (SRBI) medium with 1.0 mg l Ϫ1 6-benzylaminopurine and 0.5% (w/v) Pluronic F-68 significantly (P Ͻ 0.05) increased mean fresh weight by a maximum of 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The findings of this study are in agreement with previous reports of growth stimulation of different tissue culture material, such as isolated protoplasts of S. dulcamara (Kumar et al 1992), Petunia hybrida Anthony et al 1997), Oryza sativa (Wardrop et al 1996), callus of Capsicum annuum (Kaparakis and Alderson 2003) and S. dulcamara (Kumar et al 1992), and shoot production from cotyledon explants of Citrus depressa (Cancino et al 2001) and leaf segments of Passiflora species (Gill et al 2003). The effect of the genotype on the response to PF-68 seen in this study was also reported by Gill et al (2003) on Passiflora.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…The findings of this study are in agreement with previous reports of growth stimulation of different tissue culture material, such as isolated protoplasts of S. dulcamara (Kumar et al 1992), Petunia hybrida Anthony et al 1997), Oryza sativa (Wardrop et al 1996), callus of Capsicum annuum (Kaparakis and Alderson 2003) and S. dulcamara (Kumar et al 1992), and shoot production from cotyledon explants of Citrus depressa (Cancino et al 2001) and leaf segments of Passiflora species (Gill et al 2003). The effect of the genotype on the response to PF-68 seen in this study was also reported by Gill et al (2003) on Passiflora.…”
Section: Resultssupporting
confidence: 95%
“…(Iordan-Costache et al 1995) and chrysanthemum (Khehra et al 1995) has also been shown to be improved by supplementing media with PF-68. Shoot production was stimulated from cotyledon explants of Citrus depressa (Cancino et al 2001) and of two fiber-yielding plant species with economic value, Corchorus capsularis (Lowe et al 1993) and Hibiscus cannabinus (Khatun et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In Citrus cultivars, the multiple shoot induction has been reported to be directly proportional to the increasing levels of BA and NAA in medium (Usman et al 2005). In the case of C. depresssa, Cancino et al (2001) reported that Pluronic F-68 (0.5 %w/v) enhanced shoot regeneration in micropropagated explants cultured on MS medium with BA and significantly enhanced bud induction and the number of buds regenerated per cotyledon explants. Though, BA and Kin alone and in combination with NAA influenced shoot proliferation, shoot growth along with number of shoots induced and days taken to induction, the influence was not good enough for commercial exploitation.…”
Section: Effect Of Combination Of Ba Kinetin and Iba On Axillary Shomentioning
confidence: 99%
“…Their interaction with human cells is also well studied (reviewed in Jarak et al 2020), however, little is known about plant cells. Nevertheless, there are reports demonstrating that at specific experimental conditions, Pluronic F-68 has growth-stimulating effects on protoplasts (Kumar et al 1992, Anthony et al 1997, plant cell/ tissue cultures (Kumar et al 1992, Iordan-Costache et al 1995, Khehra et al 1995, Anthony et al 1996, Cancino et al 2001, Lee and Kim 2002, Kaparakis and Alderson 2003, Khatun et al 2003, Kok et al 2021, and microspore cultures (Barbulescu et al 2011). The effect of Pluronics on intact plants of large crabgrass was studied by Nalewaja et al (1998) who showed that Pluronic P85 was one of the most effective adjuvants tested (among five types of Pluronic polymers) for the reduction of nicosulfuron herbicide phytotoxicity.…”
Section: Introductionmentioning
confidence: 99%